Abundance, Distribution, and Diversity of Freshwater Snail and Prevalences of Their Infection by Cercaria of Fasciola gigantica and Schistosoma spp at Mayo-Vreck River, Far North Region of Cameroon - Augustin Siama; Serges Eteme Enama; Justin Kalmobe; Samuel Abah; Angele Foutchou; Alexandre Michel Njan Nloga (Journal of Tropical Medicine)
Malacological and parasitological studies were conducted from April 2020 to March 2021 to determine the abundance and distribution of molluscs and cercariae of Schistosoma spp and Fasciola gigantica. Collected molluscs are exposed to strong light to induce cercarial release. Mollusc densities were higher at station 1 (Gamak) than in station 8 (Patakai), with Bellamya unicolor and Biomphalaria pfeifferi more abundant and Bulinus truncatus, B. tropicus, and B. globosus less abundant. The overall prevalence of cercariae (19.87%) is higher in station 3 (Yaye orchard), station 9 (Gougni), station 4 (Madiogo), station 5 (Madiogo pasture), and station 6 (Ziam 3). It varies significantly between 15.76% in station 8 and 25.77% in station 3, between 8.48% in B. truncatus and 25.53% in B. globosus, and between 19.27% for cercariae of Schistosoma spp and 21.60% for those of F. gigantica. Cercarial emissions in L. natalensis and B. pfeifferi were higher in hot and cold dry seasons; on the other hand, cercarial emissions in B. globosus were higher in hot dry seasons (31.48%) and rainy seasons (23.38%). Emissions of cercariae from S. haematobium are related to areas of human activity and defecation, while those of F. gigantica in L. natalensis, Schistosoma haematobium in B. tropicus, and S. mansoni in B. pfeifferi are related to grazing areas. Mayo-Vreck is a site that favors the endemicity of fascioliasis and human schistosomiasis.